Pengaruh Bauran Pemasaran Terhadap Keputusan Menabung Nasabah Tabungan Mudharobah Koperasi Simpan Pinjam Baitul Maal Wat Tamwil Mujahidin Pontianak - Sulaiman 01 (Universitas Muhammadiyah Pontianak, 2014)
This study aims to determine the effect of the marketing mix in the customer's decision to save the savings mudharobah at BMT Mujahidin KSP Pontianak. This research uses descriptive method with data collection using observation, interviews, and questionnaires. Samples used as many as 100 people with a simple random sampling technique, the variables used in this research consists of the marketing mix (X) and consumer decision (Y). Results from this study showed that the marketing mix (X) significantly affects the decision of choosing members savings products mudharobah at KSP BMT Mujahidin (Y) with t-count is 25.485 and the value of Adjusted R Square is equal to 0.869. From the 0.932 correlation value which shows the influence of both variables between the marketing mix decisions are categorized as very strong consumer. As for the value of the coefficient of determination (KD) that is obtained is 0.869 which can be interpreted to mean that the variable X has the effect of 0.869 against the decision of choosing members savings products mudharobah at KSP BMT Mujahideen and 0.131 influenced by outside marketing mix.